Sistem Penunjang Keputusan Menentukan Karyawan Terbaik Di Dinas Perpustakaan dan Kearsipan Kota Tangerang Selatan - Hardiansyah; Ian Amukti Herlambang; Meri Hendayani; Andhika Nove Rezki; Perani Rosyani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The process of selecting the best employees is repeated every year in a long and complicated process. Therefore it really needs a decision support system in the employee selection process. Value is calculated using all existing criteria. In this study, the authors used several methods, namely Simple Additive Weight (SAW), Product Weight (WP) and Technique for Similarity Order Preference with the ideal solution method (TOPSIS). To determine the best employee, it is calculated in the way of calculating the weight of the performance rating for each alternative for all attributes. Calculation results with a larger value indicate that the alternative is preferred. In this study, determining the best employee based on the highest score. If the calculation results from all methods are the same, then this system can calculate the best worker evaluation in the library and archive services section, so that the best worker can be easily identified.